Ecossistemas comunicativos e identidades culturais: uma análise hermenêutica profunda sobre o ser jovem no semiárido paraibano - Sousa, Claviano Nascimento de (2021)
The construction of the cultural identity of young rural peasants from communicative ecosystems in the semi-arid region of Paraíba is the central theme of this research, which aims to analyze the similarities and disparities between the cultural identity of young people who integrate the ecosystem articulated by the PATAC, and young people not assisted by its actions in their territory. The stimulus for the analysis comes from the educommunicative and socio-organizational experience implemented by the NGO with the Peasant Youth Commission of the local social political actor called Regional Collective of Family Farming Organizations from Cariri, Curimataú and Seridó from Paraíba. To carry out this exploratory qualitative research, the theoretical-methodological contribution of Hermeneutics of Profundity was used (THOMPSON, 2007). The resources used, in addition to bibliographic and documentary research and Content Analysis, were questionnaires and semi-structured interviews applied to two different groups of young people. The problem of this research was to answer the question: what favors or disfavors the affirmations of the cultural identities of rural peasant youth in the semi-arid region of Paraíba? Therefore, a socio-historical understanding of the object under analysis was constructed through doxa, the investigation and mapping of the insertion of the youth theme in the projects of the NGO PATAC and, finally, the interpretation / reinterpretation of the symbolic forms produced and emitted by the public. that makes up the clipping of this research. In this sense, it is clear that the role assumed by the NGO, through the exercise of Educommunication and popular communication, is decisive in the constitution of structured communicative ecosystems and, consequently, in the construction of the peasant identity of girls and boys residing in its territory. These identities are revealed in a stronger way in the affective appreciation of the family, in the affirmation of the feelings of belonging and love for the land and in the territorial rooting of these young people. On the other hand, the lack of affirmative public policies, the incident action of the State towards these groups of young people and the impacts resulting from capitalism and the cultural industry disfavor the affirmation of their identities.